Determinants of self-care among Jordanian children with type 1 diabetes mellitus - Salam Hamdan; Esra' Taybeh; Mervat M. Alsous (SpringerOpen, 2024)
Abstract Background Diabetes Self-Care Management (DSCM) is crucial for managing diabetes mellitus and improving patients' well-being. Research on the young age group in Jordan is limited, and there is a lack of studies using an evaluation tool for understanding diabetes pharmacotherapy. This study intends to fill the information gap by examining young Jordanian patients' knowledge and comprehension of type 1 diabetes mellitus (T1DM) and its treatment modalities, evaluating their psychological well-being, and examining the relationship between children's psychological health and self-care. Methods This cross-sectional study was conducted in the Jordanian Ministry of Health hospitals in Amman from June 2021 to January 2022. A convenience sampling method was used to select Arabic-speaking diabetic patients aged 11-a8 years who provided signed consent. A sample size of 400 was estimated. A self-administered questionnaire was developed based on a literature review to assess sociodemographic characteristics and diabetes and insulin knowledge, and validated scales were used to assess self-management (SMOD-A) and psychological well-being (ChilD-S). Results Analysis of the questionnaire responses revealed varying levels of knowledge among the participants. Approximately half of the children (49.0%) demonstrated a lack of knowledge of diabetes pharmacotherapy. Psychological well-being indicators indicated moderate levels of happiness and feeling fine. The analysis of self-management indicators highlighted areas for improvement. Positive weak but significant correlations were found between children's knowledge about diabetes (r = 0.255, p < 0.01), diabetes pharmacotherapy knowledge (r = 0.125, p < 0.05), psychological well-being (r = 0.112, p < 0.05), and their diabetic self-management scores. A multivariate regression analysis identified predictors of self-management, including the child's school year (p = 0.035), ability to express feelings (p = 0.039), recent HbA1c levels (p = 0.028), and diabetes knowledge score (p < 0.001). Conclusion Participants exhibited varying levels of knowledge about diabetes pharmacotherapy and self-management. Knowledge about diabetes was identified as a predictor for effective self-management. Moreover, glycemic control and diabetes mellitus awareness majorly impact overall self-management behaviors. Tailored education programs are necessary to fill knowledge gaps and enhance diabetes management among children.